2008
DOI: 10.2332/allergolint.o-07-513
|View full text |Cite
|
Sign up to set email alerts
|

A 13-year Study of Japanese Cedar Pollinosis in Japanese Schoolchildren

Abstract: JCP sensitization appeared to be associated with the recent birth cohort and to increases in dispersed pollen just after birth and in the observed season. Although the recent birth cohort was more easily sensitized, they were not more likely to develop symptoms. In contrast to JCP sensitization, strong HDM sensitization appeared to develop prior to commencement of primary school and was more likely to affect boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…In a previous study, no significant difference in the prevalence of atopic dermatitis between boys and girls in Japan was reported [24]. However, the prevalence of asthma and rhinitis in boys was greater than that in girls [25][26][27]. Similar to previous studies, our study showed a higher symptom prevalence among boys than girls.…”
Section: Discussionsupporting
confidence: 80%
“…In a previous study, no significant difference in the prevalence of atopic dermatitis between boys and girls in Japan was reported [24]. However, the prevalence of asthma and rhinitis in boys was greater than that in girls [25][26][27]. Similar to previous studies, our study showed a higher symptom prevalence among boys than girls.…”
Section: Discussionsupporting
confidence: 80%
“…Over the same period, however, rhinitis and itching eyes in spring and autumn, of the pollinosis type, continued to increase. In Japan, pollen of the Japanese cedar ( Cryptometria japonica ) and the Japanese cypress ( Chamaecyparis obtusa ), which shares common antigenicity with the Japanese cedar, spreads ubiquitously through the air at high levels from February to May, and the number of pollinosis patients has increased over the past 40 yr to become a major concern (22–24). Some 70% of the land surface of Japan is covered in forest, and 28% of those forests are made up of plantations of the Japanese cedar and the Japanese cypress (Japanese Forestry Agency: ‘State of Forestry Resources’ 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in allergic diseases in Japan has recently been reported [1][2][3]; 3-4% of the population have symptoms of asthma, about 30% suffer from allergic rhinitis, and 20% of schoolchildren or junior high-school students have atopic dermatitis. In general, allergic disease is benign, but quality of life decreases remarkably due to cough, mucus and pruritus.…”
Section: Introductionmentioning
confidence: 99%